2019
DOI: 10.1371/journal.pone.0217854
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal temperatures and hydrological conditions improve the prediction of West Nile virus infection rates in Culex mosquitoes and human case counts in New York and Connecticut

Abstract: West Nile virus (WNV; Flaviviridae : Flavivirus ) is a widely distributed arthropod-borne virus that has negatively affected human health and animal populations. WNV infection rates of mosquitoes and human cases have been shown to be correlated with climate. However, previous studies have been conducted at a variety of spatial and temporal scales, and the scale-dependence of these relationships has been understudied. We tested the hypothesis that climate variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 101 publications
(131 reference statements)
5
52
1
2
Order By: Relevance
“…Meteorological data was obtained from a weather station that was located 1.3 km east and 3.2 km north of the Hayward Marsh using the US National Centers for Environmental Information database (www.ncdc.noaa.gov/cdo-web; [29]). Cumulative degree-days (DD) for each week was calculated as described previously for Culex mosquitoes [30] by comparing the daily average temperature to a baseline of 10°C (See Equation 1). If the DD calculation resulted in a negative value, zero was used instead.…”
Section: Methodsmentioning
confidence: 99%
“…Meteorological data was obtained from a weather station that was located 1.3 km east and 3.2 km north of the Hayward Marsh using the US National Centers for Environmental Information database (www.ncdc.noaa.gov/cdo-web; [29]). Cumulative degree-days (DD) for each week was calculated as described previously for Culex mosquitoes [30] by comparing the daily average temperature to a baseline of 10°C (See Equation 1). If the DD calculation resulted in a negative value, zero was used instead.…”
Section: Methodsmentioning
confidence: 99%
“…The RF model is a new regression method and can address the limitations of ARIMA/X models in the prediction of diarrhea incidence [11][12][13][14]. It can effectively extract non-linear relationships from data.…”
Section: Introductionmentioning
confidence: 99%
“…Using the RF model, the training set for each tree is randomly selected from the data, and the final predicted value is the average of all CART outputs. RF model has been widely used for infectious-disease prediction such as West Nile virus infection and Bovine viral diarrhea [12,13]. Notably, Michael et al [14] reported that an RF model has advantages over the ARIMA model in predicting avian influenza H5N1 outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…Random forest (RF) model can effectively extract nonlinear relationships in data, which starts by creating classification and regression trees and each constituent tree trains on a potentially nonlinear regression space and is then combined with others. It has been widely used in infectious diseases prediction such as to predict West Nile virus infection and avian influenza incidence [10][11].…”
Section: Introductionmentioning
confidence: 99%